1979
DOI: 10.1530/jrf.0.0560193
|View full text |Cite
|
Sign up to set email alerts
|

The lack of effect of ejaculate sequence on sex ratio in rabbits

Abstract: Summary. The influence of the order of the ejaculate on the sex ratio was determined by ejaculating 1 of 5 experimental males 20 times over a period of 2 to 8 h. The sex ratio was noted for the offspring of ejaculates 1, 5, 10, 15 and 20 in a total of 32 litters. The sex ratio of these offspring did not deviate significantly from 50:50 (P > 0\m=.\1) for any ejaculate in the sequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Hays observed that a higher frequency of sexual activity in male rabbits was associated with a higher proportion of female offspring, while not being able to explain that phenomenon [ 40 ]. Later, D’Amato et al performed a similar experiment but did not find a significant correlation between the sex of the offspring and the frequency of ejaculation or sexual activity of male rabbits [ 41 ]. Therefore, he discouraged the use of this method to control the sex ratio in rabbits [ 41 ].…”
Section: Attempts For Sexing Rabbit Spermatozoamentioning
confidence: 99%
See 1 more Smart Citation
“…Hays observed that a higher frequency of sexual activity in male rabbits was associated with a higher proportion of female offspring, while not being able to explain that phenomenon [ 40 ]. Later, D’Amato et al performed a similar experiment but did not find a significant correlation between the sex of the offspring and the frequency of ejaculation or sexual activity of male rabbits [ 41 ]. Therefore, he discouraged the use of this method to control the sex ratio in rabbits [ 41 ].…”
Section: Attempts For Sexing Rabbit Spermatozoamentioning
confidence: 99%
“…Later, D’Amato et al performed a similar experiment but did not find a significant correlation between the sex of the offspring and the frequency of ejaculation or sexual activity of male rabbits [ 41 ]. Therefore, he discouraged the use of this method to control the sex ratio in rabbits [ 41 ].…”
Section: Attempts For Sexing Rabbit Spermatozoamentioning
confidence: 99%